MENGUAK PERAN ULAMA DI GAYO ANALISIS SOSIAL DAN HISTORIS (Sekolah Tinggi Agama Islam Negeri (STAIN) Teungku Dirundeng Meulaboh Aceh Barat, 2020)
The Gayo people are people who live in the highlands of Aceh province. Islamic identity for the Gayo community has existed since the 11th century AD, the Gayo community pays great respect to religious leaders. This can be seen in various aspects, one of which is in government, known as sarak opat. The role of ulama in Gayo is classified in several ways: In the context of the Gayo community, ulama have a role as religious educators, as politicians, as religious officials and as government officials and most ulama in Gayo are classified as free ulama. The publicâ€™s recognition of the predicate â€œfree ulamaâ€ for someone is based on deep knowledge, noble character and high adherence to religious teachings, and is not tied to the government bureaucracy as an official.